2016
DOI: 10.1002/bip.22770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a degrading enzyme in human serum that hydrolyzes a C‐terminal core sequence of neuromedin U

Abstract: Neuromedin U (NMU), an anorexigenic peptide, has attracted attention as a candidate for development of drugs against obesity. We recently developed several potent hexapeptidic agonists derived from NMU that share a common Pro-Arg-Asn-NH2 (PRN) sequence at their C-termini and found that the amide bond between Arg and Asn is rapidly degraded in serum. In this study, we determined that the key enzyme responsible for this biodegradation was thrombin. Both irreversible and reversible thrombin inhibitors (PPACK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 25 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…Moreover, it was reported that the preferential biodegradation site of this NMUR1 selective agonist was located between the Arg and Asn residues and that the key enzyme, responsible for this cleavage, was found to be thrombin [20,36]. The present study is giving more accurate information when compared to studies where experiments were performed with 25% rat or human serum [19,20]…”
Section: In Vitro Plasma Stabilitymentioning
confidence: 62%
“…Moreover, it was reported that the preferential biodegradation site of this NMUR1 selective agonist was located between the Arg and Asn residues and that the key enzyme, responsible for this cleavage, was found to be thrombin [20,36]. The present study is giving more accurate information when compared to studies where experiments were performed with 25% rat or human serum [19,20]…”
Section: In Vitro Plasma Stabilitymentioning
confidence: 62%
“…Finally, we detected endogenous secretion of NMU in response to a mixed meal, showing that NMU can be considered as an enteropeptide. After a mixed meal, NMU was only detected in the portal vein that receives peptide secretions from the gut and not in the general blood circulation, confirming its rapid degradation (33). In addition, and as recently reported by Kuhre et al .…”
Section: Discussionmentioning
confidence: 91%
“…We here show that intra‐NAc NMU attenuates acute and chronic effects of alcohol; however, the origin of NMU detected in the NAc could include neuronal production or peripheral release. As the circulating NMU levels are low due to rapid degradation, the possibility that NMU is produced locally in distinct brain regions appears more likely. NMU coreleasing afferents of the lateral hypothalamus, an area that regulates drug reinforcement through its NAc projection, may provide one tentative origin.…”
Section: Discussionmentioning
confidence: 99%